The Impact of ChatGPT on English Language Learners’ Writing Skills: An Assessment of AI Feedback on Mobile - Jamshed, Mohammad; Abu Saleh Md Manjur Ahmed; Md Sarfaraj; Wahaj Unnisa Warda (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Artificial intelligence (AI) has shown promise in enhancing English as a second language (ESL) writing skills by providing personalized feedback and targeted corrections, thereby facilitating improved grammar and composition proficiency. Despite the potential of AI tools like ChatGPT, their impact on common writing errors in ESL contexts has yet to be explored. This study employed a quasi-experimental design to compare the efficacy of ChatGPT’s mobile application feedback against traditional teacher feedback in a senior secondary public school in India. Over eight weeks, the experimental group received feedback on their writing error corrections through the ChatGPT application, while the control group received feedback from teachers. Additionally, participants’ attitudes towards using ChatGPT for language learning were assessed through a questionnaire administered post-intervention to 132 students. Data was collected using pre- and post-tests that involved writing stories based on pictures. The study results demonstrated that the experimental group significantly improved writing proficiency, showing a reduction in common errors (third-person singular present, past tense, progressive, past participle, plural, possessive, comparative, and superlative) compared to the control group. Furthermore, most students preferred AI feedback, associating it with noticeable improvements in their writing skills and grammatical accuracy. These findings support the integration of AI tools like ChatGPT into language learning curricula as effective supplements to traditional teaching methods, offering personalized and immediate corrections that enhance learning outcomes.